2023
DOI: 10.3389/fpubh.2023.1165892
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of different exercise forms on executive function and the mechanism of cerebral hemodynamics in hospitalized T2DM patients: a within-subject study

Abstract: ObjectiveThis study aimed to investigate the acute effects of aerobic exercise (AE), resistance exercise (RE), and integrated concurrent exercise (ICE; i.e., AE plus RE) on executive function among hospitalized type 2 diabetes mellitus (T2DM) inpatients, and the mechanism of cerebral hemodynamics.MethodsA within-subject design was applied in 30 hospitalized patients with T2DM aged between 45 and 70 years in the Jiangsu Geriatric Hospital, China. The participants were asked to take AE, RE, and ICE for 3 days at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The common carotid artery is the main channel for blood supply to the brain. Previous studies have found that aerobic exercise, resistance exercise, and integrated concurrent exercise could immediately increase blood supply to the brain ( Wang et al, 2023 ), and high-intensity interval exercise might be beneficial for brain-related health as maintenance of cerebral perfusion in contrast to high-intensity continuous exercise ( Tsukamoto et al, 2019 ). Our study shows that the Q ma x , Q mean , V max , and V mean in all trials significantly increased at 0 min, in the following order AE10 > CE > AE15.…”
Section: Discussionmentioning
confidence: 99%
“…The common carotid artery is the main channel for blood supply to the brain. Previous studies have found that aerobic exercise, resistance exercise, and integrated concurrent exercise could immediately increase blood supply to the brain ( Wang et al, 2023 ), and high-intensity interval exercise might be beneficial for brain-related health as maintenance of cerebral perfusion in contrast to high-intensity continuous exercise ( Tsukamoto et al, 2019 ). Our study shows that the Q ma x , Q mean , V max , and V mean in all trials significantly increased at 0 min, in the following order AE10 > CE > AE15.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical and preclinical analyses have employed diverse brain imaging and electrophysiological methodologies, including electroencephalography, functional MRI, and transcranial magnetic stimulation [73]. These alterations are linked with increased blood circulation and simultaneous cognitive enhancements in individuals undertaking immediate exercise, irrespective of their age [73,74]. Moreover, there is an indication that a single exercise session could foster both restraint and activation in the motor cortex, correlating with progress in motor learning and possible amplifications in cortical adaptability [73], which could be important interventions for fall prevention and for modulating some degenerative diseases, such as Parkinson's disease, in older adults [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment, in turn, negatively impacts patients’ self-care and blood glucose management, fostering a vicious cycle ( Sinclair and Abdelhafiz, 2020 ). Patients with T2DM experience varying degrees of decline in executive function, memory, and information-processing abilities ( Sadanand et al, 2016 ; Wang H. et al, 2023 ). These cognitive deficits are closely associated with changes in brain function and structure related to T2DM, such as cerebral perfusion deficits ( Cui et al, 2017 ; Wang et al, 2021 ), brain white matter damage ( Jing et al, 2022 ; Liu et al, 2024 ), and hippocampal volume atrophy ( Hirabayashi et al, 2016 ; Ohara et al, 2020 ; Zhang W. et al, 2021 ).…”
Section: Evidence Of Cognitive Decline In Diabetes Patientsmentioning
confidence: 99%
“…As mentioned earlier, CBF significantly decreases in multiple regions in patients with T2DM ( Cui et al, 2017 ; Bangen et al, 2018 ; Wang et al, 2021 ; Liu et al, 2022 ). Endothelial dysfunction and reduced CBF are considered early changes preceding the occurrence of cognitive deficits ( Sadanand et al, 2016 ; Gorelick et al, 2017 ; Wang H. et al, 2023 ). Imbalances in endothelium-derived vasoconstrictors and vasodilators can lead to cerebrovascular dysfunction, which may result in CBF dysregulation, with the endothelium being considered an early target for metabolic diseases, including diabetes ( Kiss et al, 2020b ).…”
Section: Evidence Of Cognitive Decline In Diabetes Patientsmentioning
confidence: 99%